2019
DOI: 10.36487/acg_rep/1915_03_mucina
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, biodiversity and mining: science and solving the challenges

Abstract: Mining has an impact on the ecology and biodiversity of an area, and this impact is required to be mitigated under regulatory requirements. The mitigation is achieved by applying measures, deeply rooted in scientific knowledge, of the functioning of the impacted (and rehabilitated) ecosystems and the biota supported by these ecosystems. This paper focusses on selected issues of the pre-mining ecology and biodiversity surveys and the scientific basis of regulatory requirements. Using Western Australian experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Mining limestone for cement is a major industrial activity in at least 15 countries (Mucina et al, 2019 ; Pratiwi et al, 2021 ). Today, the number of ecosystems destroyed by these mining activities is increasing, and many studies have shown negative impacts of the presence of post‐mining sites on ecosystem health (Palmer et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mining limestone for cement is a major industrial activity in at least 15 countries (Mucina et al, 2019 ; Pratiwi et al, 2021 ). Today, the number of ecosystems destroyed by these mining activities is increasing, and many studies have shown negative impacts of the presence of post‐mining sites on ecosystem health (Palmer et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecologists preferably emphasize the re‐establishment or increase of biodiversity as a goal of restoration. Biodiversity is typically associated with the increase in ecosystem functions or ecosystem services (Mucina et al, 2019 ; Pratiwi et al, 2021 ; Rey Benayas et al, 2008 ). In this regard, assessing biodiversity and ecosystem services in post‐mining sites has received wide attention among restoration scientists (Pitz et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations